Membrane ATPases and Mitochondrial Proteins in Fetal Cerebellum After Exposure to L-Glutamate During Gestation - Adrián Tejero; David Agustín León-Navarro; Mairena Martín (Membranes)
L-Glutamate (L-Glu) and its salt derivatives are widely used in the food industry as flavor enhancers. Although the consumption of these compounds is generally considered safe, some studies suggest that chronically consuming L-Glu may be associated with various disorders. In this study, Wistar pregnant rats were treated daily with 1 g/L of L-Glu in their drinking water throughout the gestational period. OPA-1, DRP-1, and mitofusin 2—key proteins involved in mitochondrial fusion and fission—were analyzed by Western blot. The results showed that L-Glu exposure significantly decreased DRP-1 levels, while OPA-1 and mitofusin 2 levels were unaffected. This was accompanied by a notable decrease in mitochondrial complexes III and V. The activities of Mg2+-ATPase and Na+/K+-ATPase were also analyzed in fetal cerebellar plasma membranes. Maternal L-Glu intake significantly increased Mg2+-ATPase activity. Regarding Na+/K+-ATPase, the data showed that L-Glu exposure did not modulate the protein level or its activity. However, a positive interaction with glutamate receptors was observed in both activities, although neither AMPA nor NMDA receptors appeared to be involved. These results suggest that chronic maternal L-Glu intake during gestation modulates Mg2+-ATPase activity and protein markers of mitochondrial dynamics in the fetal cerebellum, which could affect neonatal development.